Micropaleontological Education in Indonesia - Herman Darman (Ikatan Ahli Geologi Indonesia, 2014)
In May 2012, Bailey and Jones published an article titled “Micropalaeontology Under Threat!” in Geoscientist Online Special, which attracted a number of readers’ attention. This topic was discussed further in the Sedimentology and Paleontology Linked-in group. The article describes trends in the United Kingdom, but these are similar in many other countries. It observed how since the 1980's the employment opportunities for micropaleontologists decreased as a result of downsizing by oil companies, how training opportunities decreased due to reduction in the number of universities teaching micropaleontology courses, and how retirements of an aging population of biostratigraphers may soon lead to a shortage in experienced biostratigraphers.To understand the situation in Indonesia, the topic was launched in IAGI-net. A simple survey was run on Facebook to involve students. This article summarizes the discussion and survey to provide a general understanding and quick overview on how micropaleontological education is conducted in Indonesia.